Assessment of complement regulatory proteins CD35 and CD55 in β-thalassemia patients - Noor Jafer Mohammed; Abeer Anwer Ahmed (Iraqi Journal of Cancer and Medical Genetics, 2019)
BackgroundReduced or absent production of Beta globin chain causing a hemolytic anemia known as beta thalassemia which is an inheritedanemia of variable severity results from imbalances of globin chains, ineffective erythropoiesis and hemolysis. Red Blood cellsare protected from lysis caused by complement via the complement regulatory proteins CD35 and CD55.Aim of the studyTo evaluate CD35 and CD5 in beta thalassemia cases and correlate the serum level of CD35 and CD55 with clinical and hematologicalparameters.Patients and methodsA case control study , included 60 patients who were a known case of β-thalassemia aged between 2_30 years and control groupof 20 participants who were healthy and age and sex matched with case group. All hematological parameters were done by automatedhematological analyzer.Serum level of CD35 and CD55wereestimated in both patients and control subjects by ELISAtechnique.ResultsIn this study, Mean RBC, Hb, PCV, MCH, and MCV were significantly lower in thalassemia cases. Serum level of CD35 wassignificantly lower ,while CD55was significantly higher in patients with thalassemia .There were significant weak positive correlationsbetween CD35and both of RBC and PCV level.ConclusionA low level of CD35 in β thalassemia patients can accelerate the RBC lysis by permitting complement deposition on them.CD35 level showed positive correlation with RBC and PCV and negative correlation with RDW. CD55 is high in thalassemiabut with no significant correlation with any of thalassemic patients’ characteristics.